2010
DOI: 10.1007/s00467-009-1304-9
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and postcaptopril renal scintigraphy as a screening test for renovascular hypertension in children

Abstract: We studied the ability of pre- and postcaptopril renal scintigraphy to predict renovascular disease (RVD) in children. Retrospective review of medical notes and radiology reports of all hypertensive children who had had both pre- and postcaptopril renal scintigraphy with [(99m)Tc] dimercaptosuccinic acid (DMSA) and/or [(99m)Tc] mercaptoacetyltriglycine (MAG3) and digital subtraction angiography (DSA). 81 children aged 1-18 (median 10) years were studied with 62% (51) having a diagnosis of RVD. Main renal arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A combination of MAG3 renal scintigraphy and captopril could have been prescribed in the past to determine the renovascular mechanism when the etiology of hypertension remained unclear. However, this has become unfavorable for the diagnosis of renal artery stenosis because more informative investigations are now available [1]. Moreover, because of the high frequency of bilateral lesions, renal function could be threatened by captopril usage.…”
Section: Discussionmentioning
confidence: 98%
“…A combination of MAG3 renal scintigraphy and captopril could have been prescribed in the past to determine the renovascular mechanism when the etiology of hypertension remained unclear. However, this has become unfavorable for the diagnosis of renal artery stenosis because more informative investigations are now available [1]. Moreover, because of the high frequency of bilateral lesions, renal function could be threatened by captopril usage.…”
Section: Discussionmentioning
confidence: 98%
“…Previous small studies have suggested that it could be useful as a screening test, but a recent large evaluation of the usefulness of this method from our institution did, however, find a sensitivity of only 47%, which thus renders this method useless [7]. The largest and best studies in adults have found sensitivity between 72 and 81%, which is also too low if a potentially curable problem is sought.…”
Section: Imagingmentioning
confidence: 70%
“…A number of studies, mainly referring to adult population, have shown different sensitivity and specificity of the captopril scintigraphy in the detection of renovascular disease 14 . The research results in the adult population as well as in the pediatric ones were quite inconsistent.…”
Section: Discussionmentioning
confidence: 99%